Corporate Governance in den Geschäftsberichten japanischer Unternehmen - Rodatz, Peter (Zeitschrift für Japanisches Recht, 2006)
The article examines corporate governance in Japan on the basis of corporations’ annual reports. The reform of Japanese company law in 2001/02 permitted corporations to choose their organizational form from two different models provided for in the law. The eleven annual reports examined show that all companies have introduced a two-level management structure with a board of directors and shikkô yakuin. However, only one of the corporations under examination followed the model as stated in the law. All other companies introduced hybrid structures. These hybrids are not provided for in the law; however, it is within the board’s competence to set up such structures. The new model introduced by the law reform is based on American structures and is intended to split executive and supervisory functions. This goal was not achieved as it is members of the board of directors that are appointed as executive officers. All in all, the reform of corporate governance does not seem to have gained ground; even where it was decided to introduce the new model, practical implementation often does not follow the reform provisions. (The Editors)